2007
DOI: 10.1080/14992020601058117
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrically equivalent Russian speech audiometry materials by male and female talkers

Abstract: Despite the large number of individuals who speak Russian, only a limited number of high-quality speech audiometry materials are available in a standard dialect of Russian. Thus, the purpose of this study was to develop and evaluate speech audiometry materials that can be used to measure word recognition and SRT testing in quiet for native speakers of Russian. Familiar monosyllabic and bisyllabic words were digitally recorded by male and female talkers of Russian and subsequently evaluated by native listeners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Harris et al (2003) developed Korean monosyllabic word lists and found that the mean slope was 5.0%/dB for a male talker and 5.1%/dB for a female talker. Harris et al (2004) also developed monosyllabic materials for native Polish speakers. The lists were found to have mean slopes of 5.8%/dB for a male speaker and 5.9%/dB for a female speaker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harris et al (2003) developed Korean monosyllabic word lists and found that the mean slope was 5.0%/dB for a male talker and 5.1%/dB for a female talker. Harris et al (2004) also developed monosyllabic materials for native Polish speakers. The lists were found to have mean slopes of 5.8%/dB for a male speaker and 5.9%/dB for a female speaker.…”
Section: Discussionmentioning
confidence: 99%
“…The lists were found to have mean slopes of 5.8%/dB for a male speaker and 5.9%/dB for a female speaker. In addition, Harris et al (2007) designed and evaluated monosyllabic materials in Russian. Mean slopes of 5.8%/dB for a male talker and 5.6%/dB for a female talker were reported.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation of the random selection procedure is that the phonemic distribution of the selected set may differ from that of the original matrix. Even though the validity of phonemic balancing as a design criterion for speech tests has been debated ( Martin, Champlin, & Perez, 2000 ; Wang, Mannell, Newall, Zhang, & Han, 2007 ) and some authors have abandoned phonemic balancing in developing speech materials ( Harris et al., 2007 ; Kirk, Pisoni, & Osberger, 1995 ; Nissen, Harris, Jennings, Eggett, & Buck, 2005 ), recent matrix tests in other languages were all developed to be phonemically balanced. Regardless of the validity of phonemic balanced speech materials, for the current optimization it is important that the differences between subset-based sampling and the original matrix test with respect to the phonemic distributions remain relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widely reported clinical value, SRT testing still faces several significant threats to its reliability and validity as a measure of speech reception. Harris et al ( 2007 ) summarised these threats to include the number, type and homogeneity of the words in the test; the accent or dialect of the speaker; and the method and level of stimulus presentation. Panday, Kathard, Pillay and Govender ( 2007 , 2009 ) provided a description of how these threats may be addressed when developing SRT tests.…”
Section: Introductionmentioning
confidence: 99%